2019
DOI: 10.1016/j.yexmp.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

TKS5-positive invadopodia-like structures in human tumor surgical specimens

Abstract: Invadopodia, cancer cell protrusions with proteolytic activity, are functionally associated with active remodeling of the extracellular matrix. Here, we show that the invadopodia-related protein TKS5 is expressed in human pancreatic adenocarcinoma lines, and demonstrate that pancreatic cancer cells depend on TKS5 for invadopodia formation and function. Immunofluorescence staining of human pancreatic cancer cells reveals that TKS5 is a marker of mature and immature invadopodia. We also analyze the co-staining p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…Emerging evidence demonstrated that invadopodia are essential for cancer cell intravasation ( Gligorijevic et al, 2014 ) and extravasation into specific microenvironments permissive for metastatic colony growth ( Leong et al, 2014 ; Williams et al, 2019 ), as reported in preclinical mouse models, both affecting the efficiency of metastasis. Moreover, results from the analysis of tumor surgical specimens strongly support the existence of invadopodia inside human tumors, further underscoring the clinical relevance of invadopodia for human tumor biology ( Chen Y.C. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…Emerging evidence demonstrated that invadopodia are essential for cancer cell intravasation ( Gligorijevic et al, 2014 ) and extravasation into specific microenvironments permissive for metastatic colony growth ( Leong et al, 2014 ; Williams et al, 2019 ), as reported in preclinical mouse models, both affecting the efficiency of metastasis. Moreover, results from the analysis of tumor surgical specimens strongly support the existence of invadopodia inside human tumors, further underscoring the clinical relevance of invadopodia for human tumor biology ( Chen Y.C. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…Collectively, these and other findings, support a role for invadopodia in cancer invasiveness and metastatic potential in vivo, and indicate that invadopodia are likely used by cancer cells inside tumors to cross the basement membrane, invade through the stroma and enter the circulation. Consistent with this hypothesis, a subset of TKS5 positive cells is found associated with the leading edge in human pancreatic adenocarcinoma surgical specimens [ 48 ]. A closer look to TKS5-stained cells in pancreatic surgical specimens revealed the presence of invadopodia-like punctate structures, further suggesting that invadopodia are elaborated by cancer cells, including PDAC, inside human tumors [ 48 , 49 , 50 ].…”
Section: Cellular Mechanisms Of Pdac Invasionmentioning
confidence: 72%
“…The long TKS5 isoform (TKS5α) is the prominent form found in cancer cells [ 44 , 45 ], and it is associated with malignant transformation and with poorer prognosis in several human malignancies including glioblastoma and breast cancer [ 41 , 46 , 47 ]. TKS5α is expressed in a number of pancreatic adenocarcinoma cell lines, and TKS5-positive invadopodia are elaborated by the pancreatic cancer cells lines BxPC3 and PANC1 [ 48 , 49 , 50 ] ( Figure 2 ). PDAC cells depleted of TKS5 fail to elaborate invadopodia and degrade gelatin substrates [ 48 ].…”
Section: Cellular Mechanisms Of Pdac Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…If invadopodia have been extensively studied in cell culture, they have now been detected using in situ tissue explants, tissues sections and in vivo models (40). By immunostaining Tks5 on PDAC surgical specimens, Chen et al observed Tks5-positive puncta associated with tumour cells and suggested the presence of invadopodia-like structures inside human tumours (41). Our data strengthen the physiological relevance of invadopodia in PDAC.…”
Section: Discussionmentioning
confidence: 99%